(untitled) (ACTA MEDICA PERUANA, 2024)
In a 5 year period of time, we operated 507 groin hernias and 36 recurrent hernias; lndirect inguinal hernia was the most frecuent. Two age groups were found to have hlgher rates of hernias: from 20 to 29, and from 60 to 69. McVay’s repalr was the most used technique. Twelve or the 39 recurrent hernias were previously repaired at other hospitals; analysls ofthe factors that caused recurrence in the patients operated upon at our hospital showed that early recurrence appeared during the first two years. Operations involvlng abdominal wall, posterior to hernial repair were a factor for recurrence, as well as operations performed by surgeons in training. Only 11 recurrences were found in the 507 operated pacientes, with a 2.2 % real recurrence rate.